IMPLEMENTATION OF PARTICIPATORY ACTION RESEARCH (PAR) IN THE DISASTER RESILIENT TOURISM VILLAGE EMPOWERMENT PROGRAM - Vina Salviana Darvina Soedarwo; Muhammad Hayat; Ratih Juliati (Jurnal Sosiologi Reflektif, 2022)
The COVID-19 pandemic has impacted many segments of society, including tourist villages in Indonesia. This condition encourages various higher education institutions to help tourism villages recover after the pandemic. UMM (University of Muhammadiyah Malang), through the MBKM (Merdeka Belajar Kampus Merdeka) Program has also participated by carrying out a series of empowerment activities to restore the economic aspects of tourist villages in Pujon, East Java. This village, during the pandemic, experienced a decrease in the number of visitors and the motivation of the managers as well. PAR (Participatory Action Research) has been chosen as an empowerment model in which researchers and informants could join in mapping the problems, finding the solutions, and formulating the joint programs. The findings showed that the PAR model used are proven to be successful in helping empower residents by increasing the motivation of village managers, using technology in marketing various products of residents, and increasing the availability of infrastructure that can improve the quality of services of tourism village managers.Pandemi Covid-19 selama dua tahun ini telah membawa dampak penurunan ekonomi pada banyak segmen masyarakat, termasuk diantaranya adalah desa wisata di Indonesia. Kondisi ini mendorong berbagai institusi pendidikan tinggi untuk membantu desa wisata pulih kembali pasca pandemi. UMM (Universitas Muhammadiyah Malang) melalui Program MBKM (Merdeka Belajar Kampus Merdeka) turut berpartisipasi dengan melakukan serangkaian kegiatan pemberdayaan dalam rangka memulihkan ekonomi desa wisata di Pujon, Jawa Timur. Desa ini selama pandemi mengalami penurunan jumlah pengunjung dan motivasi para pengelola. PAR (Participatory Action Research) telah dipilih sebagai model pemberdayaan, dimana peneliti dan subjek penelitian bersama-sama memetakan persoalan, mencari solusi, dan merumuskan program bersama. Hasil penelitian menunjukkan bahwa model PAR yang digunakan terbukti berhasil membantu memberdayakan warga, diantaranya adalah meningkatnya motivasi para pengelola desa, penggunaan teknologi untuk dapat beradaptasi dalam memasarkan berbagai produk warga, dan ketersediaan sarana prasarana yang dapat meningkatkan kualitas pelayanan dari pengelola desa wisata.